The Value of Health Insurance during a Crisis: Effects of Medicaid Implementation on Pandemic Influenza Mortality - Karen Clay; Joshua Lewis; Edson R. Severnini; Xiao Wang (Institute of Labor Economics (IZA), 2020)
This paper studies how better access to public health insurance affects infant mortality during pandemics. Our analysis combines cross-state variation in mandated eligibility for Medicaid with two influenza pandemics — the 1957-58 "Asian Flu" pandemic and the 1968-69 "Hong Kong Flu" — that arrived shortly before and after the program's introduction. Exploiting heterogeneity in the underlying severity of these two shocks across counties, we find no relationship between Medicaid eligibility and pandemic infant mortality during the 1957-58 outbreak. After Medicaid implementation, we find that better access to insurance in high-eligibility states substantially reduced infant mortality during the 1968-69 pandemic. The reductions in pandemic infant mortality are too large to be attributable solely to new Medicaid recipients, suggesting that the expansion in health insurance coverage mitigated disease transmission among the broader population.
Keywords: I13; I18; N32; N52; 330; public health insurance; medicaid; influenza pandemics